Entre o épico e o lírico : hibridismo na poesia de Leda Miranda Hühne - Bispo, Alexsandra dos Santos (2021)
The present research studies part of the poetic production of Leda Miranda Hühne, with the objective of showing that her long poems constitute cases of hybridism between the lyrical and epic genres. To this end, an analysis of the works Fim de Um Juízo (1986) and As Cantilenas do Rei-Rainha (1988) is undertaken, which reveal, among other aspects, that his poetics awakens us to a more critical socio-political awareness, allowing us to reflect on the violence of authoritarian relations as one of the hallmarks of Brazilian society. On the other hand, in aesthetic terms, both the influence of concrete poetry and the structural unity are visible in their production, which, even in cases where individually titled poems are present, give the work as a whole a principle, means and end that it dictates. the reading sequence. Thus, Hühne’s long poems, as will be demonstrated, are characterized by the hybridism between the lyric and the epic and are even inserted in the trajectory of the epic from the 20th century, when the presence of hybridity is quite relevant. In the area of literary expressions, in general, we can observe a large percentage of interpenetrations of genres. The theoretical approaches that make up this research seek, as a foundation, the dialogue between studies of criticism and literary theory, such as those of Aristotle (1973) and Staiger (1977); those of hybridism, such as those of Ramalho and Silva (2007); those of the epic genre, such as those by Bowra (1950), Gancedo (2009), Silva (2007) and Ramalho (2007, 2013), and those of the lyrical genre, such as those by Frye (1957), Friedrich (1978), Paz (1982), among others.